INFORMATICS TOOLS IN TECHNICAL AND INFORMATICS EDUCATION, DISTANCE LEARNING - PYTEL, Krzysztof (Trends in education, 2008)
In this article one introduces on area of potential of use IT in technical education. The article presents chosen answers collected from questionnaires on possibilities, functionalities and accessibilities of information technology in teaching of technical subjects.
Keywords: IT; techniques; didactics